UAV air traffic control system - subsystem - Aw, Jason Chieh Liang (2018)
An Unmanned Aerial Vehicle(UAV), commonly named as Drones, is a plane without a human pilot onboard. UAV includes an Unmanned Aircraft System, Ground-Based Controller, and a communication system between the two. It can operate either by remote control by a human operator or autonomously by onboard computers. Under Singapore Air Navigation Order, permits are needed when UAV weighs above 7KG, fly higher than 61m above mean sea level or fly a UAV within 5km of an airbase or airport. The objective of this Project is to create an Air Traffic Control application to manage UAV traffic. The pilot can register their permits and submit flight plans. There will be communication between the pilot and the air traffic controller.